2014
DOI: 10.1042/bj20140010
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of a family of major facilitator transporters in biofilm development and virulence of Candida albicans

Abstract: The QDR (quinidine drug resistance) family of genes encodes transporters belonging to the MFS (major facilitator superfamily) of proteins. We show that QDR transporters, which are localized to the plasma membrane, do not play a role in drug transport. Hence, null mutants of QDR1, QDR2 and QDR3 display no alterations in susceptibility to azoles, polyenes, echinocandins, polyamines or quinolines, or to cell wall inhibitors and many other stresses. However, the deletion of QDR genes, individually or collectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 67 publications
4
43
0
Order By: Relevance
“…It is important to point out, however, that the amount of data collected for the regulation of QDR2 in C. glabrata is resumed to a single bibliographic reference, suggesting that many more regulators of the C. glabrata QDR2 may still be uncovered. Nonetheless, the observed variability in terms of QDR2 regulation within the three species appears consistent with the fact that the function of the QDR2 gene appears also to have diverged within these yeasts (25,26,2830). …”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…It is important to point out, however, that the amount of data collected for the regulation of QDR2 in C. glabrata is resumed to a single bibliographic reference, suggesting that many more regulators of the C. glabrata QDR2 may still be uncovered. Nonetheless, the observed variability in terms of QDR2 regulation within the three species appears consistent with the fact that the function of the QDR2 gene appears also to have diverged within these yeasts (25,26,2830). …”
Section: Introductionsupporting
confidence: 71%
“…This may be extremely useful when trying to predict the function of an uncharacterized target gene/TF. For example, the recently characterized C. albicans Qdr1–3 proteins, predicted to act as Drug:H+ Antiporters (DHA) of the Major Facilitator Superfamily, were shown to play instead overlapping roles in C. albicans virulence (25). Using the Search by TF query in PathoYeastract it is possible to predict all the TFs that may play a role in the control of the transcription of QDR genes (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Prior work found that ScQDR2 is involved in maintaining copper and potassium homeostasis , but the loss of CgQDR2 does not alter the potassium homeostasis . Meanwhile, the deletion of QDR genes in C albicans has been shown to result in defects in biofilm architecture and lipid homeostasis without apparent changes in drug transport . Although the identity percentage between Ca Qdr2p and Cg Qdr2p is low (Table ), we examined whether Cg Qdr2p contributed to C glabrata biofilm formation as does Ca Qdr2p in C albicans (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…CaNag3 and CaNag4 have also been shown to be involved in C. albicans virulence, as adult mice infected intravenously with 10 6 or 10 7 cells of the Δcanag3, Δcanag4 or Δcanag3canag4 mutants lived for at least 4 weeks (in the lowest cell concentration for single mutants, and both concentrations for double mutant), compared with a maximum of 11 days for the lowest concentration of the wild type (Yamada-Okabe and Yamada-Okabe, 2002). Very recently, the deletion of C. albicans Qdr1, Qdr2, and Qdr3 transporters was found to lead to defects in biofilm architecture and thickness and to attenuate virulence in a mouse model (Shah et al, 2014). Although the exact mechanism underlying this observation was not clarified, the expression of these transporters was found to have a deep effect in membrane lipid composition, which may underly the observed phenotypes (Shah et al, 2014).…”
Section: Drug:h+ Antiporter Clinical Impact: What's Known and What Ismentioning
confidence: 99%
“…Very recently, the deletion of C. albicans Qdr1, Qdr2, and Qdr3 transporters was found to lead to defects in biofilm architecture and thickness and to attenuate virulence in a mouse model (Shah et al, 2014). Although the exact mechanism underlying this observation was not clarified, the expression of these transporters was found to have a deep effect in membrane lipid composition, which may underly the observed phenotypes (Shah et al, 2014). The C. glabrata DHA transporters CgAqr1 and CgTpo3 were also suggested to contribute to the survival of this pathogen within the host, as they confer resistance to acetic acid (Costa et al, 2013a) and polyamines (Costa et al, 2014), respectively, which accumulate to inhibitory concentrations in Candida infection prone environments.…”
Section: Drug:h+ Antiporter Clinical Impact: What's Known and What Ismentioning
confidence: 99%